Awake venoarterial extracorporeal membrane oxygenation for refractory cardiogenic shock. Issue 6 (5th April 2021) - Montero, Santiago; Huang, Florent; Rivas-Lasarte, Mercedes; Chommeloux, Juliette; Demondion, Pierre; Bréchot, Nicolas; Hékimian, Guillaume; Franchineau, Guillaume; Persichini, Romain; Luyt, Charles-Édouard; Garcia-Garcia, Cosme; Bayes-Genis, Antoni; et al.
Abstract: Background : Venoarterial-extracorporeal membrane oxygenation (VA-ECMO) is currently one of the first-line therapies for refractory cardiogenic shock (CS), but its applicability is undermined by the high morbidity associated with its complications, especially those related to mechanical ventilation (MV). We aimed to assess the prognostic impact of keeping patients in refractory CS awake at cannulation and during the VA-ECMO run. Methods : A 7-year database of patients given peripheral VA-ECMO support was used to conduct a propensity-score (PS)-matched analysis to balance their clinical profiles. Patients were classified as 'awake ECMO' or 'non-awake ECMO', respectively, if invasive MV was used during ≤50% or >50% of the VA-ECMO run. Primary outcomes included ventilator-associated pneumonia and ECMO-related complication rates, and secondary outcomes were 60-day and 1-year mortality. A multivariate logistic-regression analysis was used to identify whether MV at cannulation was independently associated with 60-day mortality. Results : Among 231 patients included, 91 (39%) were 'awake' and 140 (61%) 'non-awake'. After PS-matching adjustment, the 'awake ECMO' group had significantly lower rates of pneumonia (35% vs. 59%, P = 0.017), tracheostomy, renal replacement therapy, and less antibiotic and sedative consumption. This strategy was also associated with reduced 60-day (20% vs. 41%, P = 0.018) and 1-year mortality rates (31% vs. 54%, P = 0.021) compared to the 'non-awake' group, respectively. Lastly, MV at ECMO cannulation was independently associated with 60-day mortality. Conclusion : An 'awake ECMO' management in VA-ECMO-supported CS patients is feasible, safe, and associated with improved short- and long-term outcomes.